Affective networks, informal ties, and the limits of expatriate effectiveness. Issue 5 (October 2016) - Horak, Sven; Yang, Inju
Highlights: We study the influence of informal social networks on expatriate effectiveness. We focus on expatriate performance and adjustment. Seven antecedents are discovered critical to expatriate effectiveness. Certain informal networks appear inaccessible to expatriates in our case study. Relational performance and interaction adjustment is problematic for expatriates. Abstract: Expatriate effectiveness research has so far rarely taken into account the influence of social networks on expatriate performance and adjustment. Likewise, antecedents of social networks remain poorly understood. We fill this research gap by exploring the situation of expatriates in South Korea. Based on expert interview data, we have discovered seven antecedents critical to expatriate effectiveness. Most antecedents hinder expatriate effectiveness due to the expatriates' inability to become a part of so-called Yongo networks, a distinctive type of social tie in South Korea that is to a great extent determined by birth. As a consequence, it is in particular expatriates' relational performance and interaction adjustment that is negatively influenced by Yongo . Based on the South Korean case, this study advises future research to more deeply study the nature and characteristics of the local social context, in particular affective ties, and extend research on expatriate effectiveness in this important dimension. Finally, we discuss practical implications important for multinational corporations and provide suggestions on how to better cope with exclusive informal social networks while on an assignment abroad.